2012
DOI: 10.1371/journal.pone.0032963
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation Aggravates Disease Severity in Marfan Syndrome Patients

Abstract: BackgroundMarfan syndrome (MFS) is a pleiotropic genetic disorder with major features in cardiovascular, ocular and skeletal systems, associated with large clinical variability. Numerous studies reveal an involvement of TGF-β signaling. However, the contribution of tissue inflammation is not addressed so far.Methodology/Principal FindingsHere we showed that both TGF-β and inflammation are up-regulated in patients with MFS. We analyzed transcriptome-wide gene expression in 55 MFS patients using Affymetrix Human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
70
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 33 publications
5
70
2
Order By: Relevance
“…In contrast, Radonic, et al 11) reported very low levels of plasma TGFβ1, which were 124 pg/mL for MFS patients with aortic dilatation and 10 pg/mL for MFS patients with normal aorta using ELISA, and showed large discrepancies from the above studies. Further studies are needed to defi ne the optimal method for plasma TGFβ1 measurement.…”
Section: Discussionmentioning
confidence: 81%
“…In contrast, Radonic, et al 11) reported very low levels of plasma TGFβ1, which were 124 pg/mL for MFS patients with aortic dilatation and 10 pg/mL for MFS patients with normal aorta using ELISA, and showed large discrepancies from the above studies. Further studies are needed to defi ne the optimal method for plasma TGFβ1 measurement.…”
Section: Discussionmentioning
confidence: 81%
“…19) In addition, inflammatory T lymphocytes and macrophages reportedly infiltrate aortic media and adventitia, and those numbers were negatively correlated with patient ages at referral for prophylactic surgical repair, suggesting that inflammation might affect disease progression. 20,21) Dietz and his colleagues performed the most extensive mechanistic studies of these diseases, and identified FBN1 as a causative gene in 1991, 4) with FBN1 mutations accounting for > 60% of MFS patients. FBN1 is a 230 kb gene with 65 exons, and the encoded microfibrillar protein fibrillin-1 contains 7 TGF-β binding protein-like (TB) domains and 47 epidermal growth factor (EGF)-like domains, which are characterized by 8 and 6 conserved cysteine residues that form 4 and 3 intramodule disulfide bonds, respectively.…”
Section: Marfan Syndromementioning
confidence: 99%
“…Accordingly, treatment with a miR-29b oligonucleotide inhibitor prevented early formation of aneurysms. 41) Finally, plasma levels of TGF-β, 26) fibrillin-1 fragments, 42) macrophage colony stimulating factor (M-CSF), 21) and oxidative stress indicators 43) have been reported as useful biomarkers for disease progression in humans and animal models. C1039G/+ mice showed significant increases in activation of extracellular signal-regulated kinase 1/2 (ERK1/2) and mitogen-activated protein kinase kinase 1 (MEK1), which is the upstream activator of ERK1/2.…”
Section: ;Tgfb2mentioning
confidence: 99%
“…Loss of fibrillin-1 releases TGF-β and its constitutive stimulation activates genes like MMPs which induce elastolysis, decreasing ECM stability. and adventitia respectively [65]. Furthermore, the interleukin-6/STAT3 signaling pathway was recently implicated in aortic dilation through increased MMP-9 activity in MFS mice [66].…”
Section: Other Variables In Mfsmentioning
confidence: 99%